Pengelolaan dan Penyajian Laporan Keuangan Pesantren Berbasis Akuntansi Syariah : Analisis Kritis Pedoman Akuntansi Pesantren - senjiati, Ifa hanifia; maulida, ira siti rohmah; Suhatman, zaldy; ridwan, itsnaina lathifah (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
The potential of managing pesantren, especially in West Java, reaches 8342 pesantren with 453,981 students. Then it needs improvement in financial management because there are still many pesantren that have not been as good as Nurul Hijrah Islamic Boarding School in East Jakarta. During this time, the pesantren presents financial reports based on PSAK 45 and PSAK Entities without a Public Accountant (ETAP). However, some pesantren have not carried out financial reporting as in the related PSAK. The research method used is qualitative with a descriptive approach. Stages of research include literature review, formulation of research problems, preparation of research methods and instruments, data analysis, and concluding. Data collection techniques through surveys of pesantren in Depok City. Data analysis uses narrative analysis. The results of the study are that pesantren financial managers generally do not have an accounting or financial education background, financial management is manually systemized or an excel application, and there is no internet connection. The financial management of pesantren in Depok is decentralized and centralized. Islamic boarding school-based financial management is the presentation of financial statements prepared based on PSAK 45 related to non-profit organizations, PSAK ETAP, and PSAK Syariah from PSAK 101 to PSAK 112 about Waqf. So some accounts are added such as murabahah, salam, and istishna accounts; mudharabah and musyarakah investments; ijarah assets; endowments; receipt of zakat, infaq, and shodaqoh; qard receivables; musyarakah mutanaqisoh investment and temporary syirkah funds.